2002
DOI: 10.1161/01.cir.0000023891.80661.ad
|View full text |Cite
|
Sign up to set email alerts
|

Successful Cardiopulmonary Resuscitation After Cardiac Arrest as a “Sepsis-Like” Syndrome

Abstract: Background-We investigated the immunoinflammatory profile of patients successfully resuscitated after cardiac arrest, representing a model of whole-body ischemia/reperfusion syndrome. Methods and Results-Plasma cytokine, endotoxin, and ex vivo cytokine production in whole-blood assays was assessed in 61, 35, and 11 patients, respectively. On admission, high levels of plasma interleukin (IL)-6, IL-8, IL-10, and soluble tumor necrosis factor (TNF) receptor type II could discriminate between survivors and nonsurv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
545
3
22

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 848 publications
(609 citation statements)
references
References 22 publications
26
545
3
22
Order By: Relevance
“…However, we did not find significant correlations between HSP70 and APACHE II or SAPS II scores, i.e., two correlates of clinical severity. In agreement with previous observations (Adrie et al 2002), we also found higher CRP, and S100B levels in nonsurvivors than in survivors, indicating that the severity of cellular damage and/or host response to this damage is detrimental, as regards survival. Considering these associations between the biomarkers and mortality, we performed Cox regression analysis to investigate the potential influence of the covariates.…”
Section: Discussionsupporting
confidence: 93%
“…However, we did not find significant correlations between HSP70 and APACHE II or SAPS II scores, i.e., two correlates of clinical severity. In agreement with previous observations (Adrie et al 2002), we also found higher CRP, and S100B levels in nonsurvivors than in survivors, indicating that the severity of cellular damage and/or host response to this damage is detrimental, as regards survival. Considering these associations between the biomarkers and mortality, we performed Cox regression analysis to investigate the potential influence of the covariates.…”
Section: Discussionsupporting
confidence: 93%
“…CA results in a rapid and complete loss of oxygen and severe energy deficit, which leads to interruption of cellular function, membrane and pump dysfunction, and increased free radical generation to induce neuronal injury 5, 47, 48. The resultant energy deficiency will elevate the AMP/ATP ratio to activate AMPK in the brain 21.…”
Section: Discussionmentioning
confidence: 99%
“…The post-cardiac arrest syndrome has pathophysiologic characteristics similar to those seen in sepsis. [18][19][20] Figure 1 Post-cardiac arrest syndrome. If return of spontaneous circulation is achieved rapidly after the onset of cardiac arrest, post-cardiac arrest syndrome will not occur.…”
Section: Post-cardiac Arrest Syndromementioning
confidence: 99%
“…Proinflammatory cytokines are produced in the presence of free oxygen radicals. 18,19 Injured neurons may recover, die as a result of lysis causing regional damage in surrounding tissues, or die via apoptosis. Capillary beds may also restore perfusion or remain occluded.…”
Section: Post-cardiac Arrest Syndromementioning
confidence: 99%
See 1 more Smart Citation